Impact of the COVID-19 Pandemic on the Socio-Economic Conditions of Farmers and Alternatives for Their Recovery in Deli Serdang District - Hotden Leonardo Nainggolan; Albina Ginting; Susana Tabah Trina; Yanto Raya Tampubolon; Tavi Supriana (Universitas Pendidikan Ganesha, 2022)
The COVID-19 pandemic has caused various negative impacts on people, both those living in urban areas and farmers in rural areas. This study aims to determine the socio-economic impact of the COVID-19 pandemic on farmers and to find alternative approaches to recovering the socio-economic conditions of farmers in the District of Deli Serdang, North Sumatra Province. The research was conducted from June to November 2021 in the District of Deli Serdang. The data used in this research are primary and secondary data, which were analyzed by descriptive methods with qualitative and quantitative approaches to determine the pandemic's impact on social and economic conditions. Statistical tests were carried out to compare the socio-economic conditions of farmers before and during the pandemic with the t-test. Based on the study's findings, it was determined that the COVID-19 pandemic had negatively impacted farmers' socio-economic conditions, which are demonstrated by a decline in their frequency of social interactions, frequency of community visits, family income, and level of savings during the pandemic. Moreover, the recovery of the social-economic conditions of farmers during the COVID-19 pandemic has been achieved through farmer empowerment activities, market development, and institutional and capital sources aspects. Based on the research results, there are three recommendations. Restoration of the socio-economic conditions of farmers will be optimal if carried out collaboratively between the government, the private sector, and the farmers themselves. The government must optimize the empowerment of farmers through training, counseling, and innovation in farming technology. Private institutions are expected to participate in socialization and counseling about optimal farming development during the COVID-19 pandemic.